2016
DOI: 10.3892/ol.2016.4273
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell vaccine and cytokine-induced killer cell therapy for the treatment of advanced non-small cell lung cancer

Abstract: Abstract. The present study aimed to evaluate the survival time, immune response and safety of a dendritic cell (DC) vaccine and cytokine-induced killer (CIK) cell therapy (DC-CIK) in advanced non-small cell lung cancer (NSCLC). The present retrospective study enrolled 507 patients with advanced NSCLC; 99 patients received DC-CIK [immunotherapy group (group I)] and 408 matched patients did not receive DC-CIK, and acted as the control [non-immunotherapy group (group NI)]. Delayed-type hypersensitivity (DTH), qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…CIK are autologous T cells, NK cells and NKT cells activated and expanded ex-vivo under the influence of anti-CD3 stimulation and cytokines. The DC-CIK combined vaccine has been shown to elicit far less adverse events as compared to standard chemotherapy and has shown promising potential in terms of improving over all survival and quality of life when tested in patients [124, 125]. Adoptive transfer of tumor specific T cells or T cells with engineered T cell receptor [126] in combination with TAA loaded DCs is yet another attractive immunotherapy option that has gained momentum due to its anti-tumor effects and usefulness even in advanced tumors [127].…”
Section: Re-emergence Of Dendritic Cell Targeting Vaccinesmentioning
confidence: 99%
“…CIK are autologous T cells, NK cells and NKT cells activated and expanded ex-vivo under the influence of anti-CD3 stimulation and cytokines. The DC-CIK combined vaccine has been shown to elicit far less adverse events as compared to standard chemotherapy and has shown promising potential in terms of improving over all survival and quality of life when tested in patients [124, 125]. Adoptive transfer of tumor specific T cells or T cells with engineered T cell receptor [126] in combination with TAA loaded DCs is yet another attractive immunotherapy option that has gained momentum due to its anti-tumor effects and usefulness even in advanced tumors [127].…”
Section: Re-emergence Of Dendritic Cell Targeting Vaccinesmentioning
confidence: 99%
“…Combination therapy with CIK cells and DC vaccine has been successfully applied to treat cancers, such as glioblastoma, non-small-cell lung cancer, and advanced renal cell carcinoma, and it has been demonstrated that this therapy can enhance host cellular immune responses, prolong survival time, and improve quality of life. 19 , 40 , 45 , 49 Mao et al 20 reported that DC vaccine and CIK cell combined with chemotherapy are able to improve the disease control rate (DCR) and living quality of patients, with no severe side effects in patients with metastatic breast cancer. However, recent clinical trials on the DC vaccine and CIK cells in CRC patients are still based on small sample size and a lack of high-quality data from multicenter studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study reported that DC-CIK might induce an immune response against NSCLC. 8 However, we cannot ignore the importance of SABR and DC-CIK immunotherapy. In our case, DC-CIK was administered 6 months before SABR and both the tumors didn't shrink, which is more supportive of an abscopal effect.…”
Section: Discussionmentioning
confidence: 99%